Management of acute cardiac tamponade by direct autologous blood transfusion in interventional electrophysiology. (22nd July 2019) - Beyls, Christophe; Hermida, Alexis; Duchateau, Josselin; Maury, Philippe; Taieb, Jérôme; Laurent, Gabriel; Kubala, Maciej; Ben Amar, Amar; Sacher, Frederic; Jais, Pierre; Hermida, Jean‐Sylvain
Abstract: Aims: Acute cardiac tamponade (ACT) is the most common life‐threatening complication of interventional electrophysiology. Urgent drainage by percutaneous pericardiocentesis and anticoagulation reversal are required. Immediate direct transfusion of the blood volume aspirated from the pericardial space to the patient has been rarely described. This study was designed to assess the efficacy and safety of immediate direct autologous blood transfusion (AutoBT). Methods: A retrospective case series of direct AutoBT performed for ACT was collected. Urgent drainage by percutaneous pericardiocentesis and immediate direct AutoBT were performed to achieve hemodynamic stabilization without a cell‐saver system. Results: Twenty‐two electrophysiology centers were contacted to participate in the case series. Fourteen centers reported not to use direct AutoBT. Three centers reported using direct AutoBT with the cell‐saver system. Fourteen cases of immediate direct AutoBT without cell‐saver system were included from the five remaining centers. Electrophysiological procedures were performed for ventricular tachycardia (n = 5), atrial fibrillation (n = 5), atrial tachycardia (n = 2), left accessory pathway (n = 1), and premature ventricular contraction (n = 1) with transseptal (n = 9), retroaortic (n = 4), and/or epicardial access (n = 4). Pericardial drainage was performed by percutaneous pericardiocentesis for 13 patients and via the transseptal sheath for one patient. Surgical hemostasis was required for seven patients. The mean volume of autologous blood directly transfused was 1207 ± 963 mL. Direct AutoBT permitted to resume the procedure in four patients. No major complication related to the use of AutoBT occurred. Conclusion: Direct AutoBT without a cell‐saver system is a feasible, safe, and useful technique for salvage therapy in ACT in interventional electrophysiology.